Examining the Schoolwide Expectations Survey for Specific Settings: Descriptive Properties. (October 2022) - Royer, David James; Lane, Kathleen Lynne; Oakes, Wendy Peia; Jenkins, Abbie Brooke; Cantwell, Emily Dawn; Common, Eric Alan; Lane, Katie Scarlett
In tiered systems, all school faculty and staff ideally recognize student academic, behavioral, and social achievement as a shared responsibility. In an ideal system, faculty and staff collaborate in a data-informed process to define common student expectations to facilitate success. Adults provide clarity for all students by defining expectations for instructional and non-instructional settings, allowing equitable access to all areas of the school experience. In this replication study, we explored educator priorities of behavioral expectations in classroom and non-instructional settings for students as measured by the Schoolwide Expectations Survey for Specific Settings (SESSS). We analyzed faculty and staff data from 10 U.S. schools whose leadership teams participated in a yearlong professional learning series to design their Comprehensive, Integrated, Three-Tiered (Ci3T) model of prevention. Results indicated educators across school levels (elementary, middle, high) had similar views on what expectations should be prioritized for student success, with statistically significant differences found for the hallway setting. Implications and future directions for research in this area are discussed.